CLEAN AND HEALTHY LIVING BEHAVIOR IN THE FAMILY ENVIRONMENT AS A PREVENTION OF COVID-19 IN SERANG CITY - Afrizal, Stevany; Athallaisya Adinda, Inez (Transpublika Publisher, 2022)
The rapid spread of the COVID-19 virus throughout the world has come as a complete shock, and it is causing serious concerns. The COVID-19 virus can be prevented with the help of a simple yet highly successful method called